Reassessing Intellectual Continuities Between Kalimantan Qur'anic Scholars and the Muhammadiyah Interpretive Tradition - Hartafan, Azmil Iman; Nirwana AN, Andri; Rhain, Ainur (QiST: Journal of Quran and Tafseer Studies, 2025)
This comparative study analyzes the relevance of the methodology of the interpretation of two Kalimantan scholars, Sheikh Muhammad Arsyad al-Banjari (pre-modern) and Muhammad Basiuni Imran(transitional era), with the framework of muhammadiyah interpretation (modern), focusing on two problem formulations: (1) the intellectual relationship and methodological relevance between the three, and (2) the relevance of their interpretation methods to the development of religion in Kalimantan. With a qualitative method based on literature studies and content analysis, this study finds that there is an intellectual common thread in the spirit of tajdid, the use of rationality, and contextualization, but with fundamental differences in the institutional model in which Muhammadiyah has succeeded in building a sustainable collective model, in contrast to the individual model of the two ulama. The implications of this research offer a historical perspective for the development of a contextual and moderate Indonesian Islamic discourse, as well as conclude that the thoughts of the two scholars have a deep compatibility with Muhammadiyah, whose excellence lies in the ability to institutionalize the intellectual heritage adaptively.